2014
DOI: 10.1039/c3nr03620k
|View full text |Cite
|
Sign up to set email alerts
|

Facile and novel electrochemical preparation of a graphene–transition metal oxide nanocomposite for ultrasensitive electrochemical sensing of acetaminophen and phenacetin

Abstract: A facile and novel preparation strategy based on electrochemical techniques for the fabrication of electrodeposited graphene (EGR) and zinc oxide (ZnO) nanocomposite was developed. The morphology and structure of the EGR-based nanocomposite were investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (XPS) and Raman spectroscopy. Meanwhile, the electrochemical performance of the nanocomposite was demonstrated with cyclic voltammetry (CV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…According to the equation (2), the slope is calculated to be 0.666 which indicates that the oxidation of ACTM on the PtÀ RGO/GCE is a combination of diffusion and adsorption controlled process. This result is found to be in good agreement with those reported literature [13,46]. Also, it was reported that the number of electrons (n) taking part in the oxidation process can be calculated according to the equation [43] below:…”
Section: The Electrochemical Behaviour Of Actm At Ptà Rgo/gcesupporting
confidence: 91%
“…According to the equation (2), the slope is calculated to be 0.666 which indicates that the oxidation of ACTM on the PtÀ RGO/GCE is a combination of diffusion and adsorption controlled process. This result is found to be in good agreement with those reported literature [13,46]. Also, it was reported that the number of electrons (n) taking part in the oxidation process can be calculated according to the equation [43] below:…”
Section: The Electrochemical Behaviour Of Actm At Ptà Rgo/gcesupporting
confidence: 91%
“…[1][2][3][4][5] Compared with the conventional piezoresistive sensing materials, such as metals, alloys, and inorganic semiconductor materials, sensors made of multifunctional CNT/polymer composites are lightweight, compact, mechanically durable and easily conformable for desired shapes and applications. For instance, they can be directly embedded in structural composites to provide real-time internal strain sensing for structural health monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The linear range obtained for the proposed sensor is similar of others reported modified electrodes. The LOD obtained in this work is higher than the modified electrode with graphene [56,63] and Nano-TiO2 [48], however the proposed sensor exhibit lower LOD value than other modified electrodes which could confirm that fMWCNT- [BMIM]PF6/GCE have high electrocatalytic and surface effects. Therefore, the fMWCNT- [BMIM]PF6/GCE showed sensitivity up to 40 times higher when compared to ACOP sensors modified with metallic nanoparticles [62] for the determination of ACOP.…”
Section: Effect Of the Scan Ratementioning
confidence: 64%